2021
DOI: 10.1016/j.crwh.2021.e00309
|View full text |Cite
|
Sign up to set email alerts
|

Critical respiratory failure in pregnancy complicated with COVID-19: A case report

Abstract: The case is presented of a 29-year-old primiparous woman who was COVID-19-positive at 34 weeks of gestation and who developed severe acute respiratory distress syndrome. After a four-day history of fever and mild dyspnea, she was referred to hospital. Ciclesonide, dexamethasone, heparin sodium, and sulbactam/ampicillin were initiated, followed by remdesivir and tocilizumab. On the fourth day after admission (at 34 weeks 5 days of gestation), respiratory failure required ventilator management. An emergency cesa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 14 publications
0
20
0
Order By: Relevance
“…Most of these observational studies (2 cohort studies, 4 case series, and 4 case reports) were conducted in the United States [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 25 , 28 ]. Other case reports were conducted in Indonesia [ 24 ], India [ 26 ], and Japan [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Most of these observational studies (2 cohort studies, 4 case series, and 4 case reports) were conducted in the United States [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 25 , 28 ]. Other case reports were conducted in Indonesia [ 24 ], India [ 26 ], and Japan [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…All 13 observational studies reported clinical outcomes [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ]. Cohort studies that compared oxygen needs between pregnant and postpartum women used a modified ordinal scale with the following criteria: (6) death; (5) hospitalized, requiring mechanical ventilation (intermittent mandatory ventilation) and/or extracorporeal membrane oxygenation; (4) hospitalized, requiring high-flow oxygen therapy and/or noninvasive positive pressure ventilation; (3) hospitalized, requiring supplemental low-flow oxygen therapy; (2) hospitalized on room air; (1) discharge.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations